2000
DOI: 10.1046/j.1365-3024.2000.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Loa loa experimental infection in mandrills (Mandrillus sphinx) vaccinated with irradiated infective larvae

Abstract: In order to shed light on the mechanisms of antifilarial protective immunity, we investigated the course of experimental loaiosis after vaccination in a nonhuman primate host, Mandrillus sphinx. Six vaccinated (V) mandrills received 50 irradiated L3 while six nonvaccinated (NV) received saline solution on days -60, -30 and -15. All animals were challenged with 100 intact L3 (day 0). Parasitological and immunological status were followed for 9 months. Vaccination delayed the appearance and mean peak of microfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Anti-Mf immunity against the bovine parasite Onchocerca lienalis has been successfully induced in mice by homologous immunization by using live L 3 (45), presumably as a result of antigenic crossreactivity between these life-cycle stages. Furthermore, inoculation of mandrills with irradiated L 3 of Loa loa resulted in the delayed onset of microfilaraemia after challenge (28). However, it is also possible that immune-mediated damage directed against challenge larvae in the current study resulted in impaired fecundity of the adult ''breakthrough'' infections, as has been reported in the L. sigmodontis model (46), and this is certainly consistent with the reduced numbers of gravid females recovered from vaccinated animals.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Anti-Mf immunity against the bovine parasite Onchocerca lienalis has been successfully induced in mice by homologous immunization by using live L 3 (45), presumably as a result of antigenic crossreactivity between these life-cycle stages. Furthermore, inoculation of mandrills with irradiated L 3 of Loa loa resulted in the delayed onset of microfilaraemia after challenge (28). However, it is also possible that immune-mediated damage directed against challenge larvae in the current study resulted in impaired fecundity of the adult ''breakthrough'' infections, as has been reported in the L. sigmodontis model (46), and this is certainly consistent with the reduced numbers of gravid females recovered from vaccinated animals.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, O. volvulus (25), Brugia pahangi (26), and Litomosoides sigmodontis (27) have been used in murine (surrogate) hosts. Natural host-filaria systems in which significant protection has been demonstrated include Loa loa in mandrills (28), Acanthocheilonema viteae in jirds (29), and Dirofilaria immitis (30) in dogs. However, in this report, the irradiated L 3 vaccine is shown to reduce the burden of a filarial infection under conditions of intensive field challenge and in a natural Onchocerca sp.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to induce protection induced by γ-irradiated infective stages were performed in some parasites, Fasciola hepatica, S. mansoni, S. japonicum, Loa loa, Brugia malayi, Achantocheilonema viteae, B. pahangi (Creaney et al 1995, Zhang et al 1999, Ungeheuer et al 2000. In these studies, that the infective larvae when optimally attenuated cannot develop into adults will die in the host, which induce high level of protection was proved.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine studies in this model have been limited to vaccination with irradiated L3 larvae. Three different trials have been performed, in which mandrills were vaccinated with 50 to 150 L3s irradiated with 40 to 45 kilorads (221,222,227). These studies showed a delay in peak microfilaremia in the vaccinated mandrills but no significant decrease in microfilaremia.…”
Section: Loa Loamentioning
confidence: 99%